PEMANFAATAN POJOK BACA SEBAGAI TEMPAT MENUMBUHKAN BUDAYA LITERASI DAN INTELEKTUALITAS PADA SISWA SD N 1 TANJUNG ALAI (DI DESA TANJUNG ALAI KECAMATAN SIRAH PULAU PADANG KABUPATEN OGAN KOMERING ILIR) - Sabrina, Amirah (HYPOTHESIS : Multidisciplinary Journal Of Social Sciences, 2025)
This study aims to determine the utilization of the Reading Corner as a means of fostering a culture of literacy and intellectuality of students at SD Negeri 1 Tanjung Alai, Tanjung Alai Village, Sirah Pulau Padang District, Ogan Komering Ilir Regency. The method used in this research is descriptive qualitative method with data collection techniques through observation, interviews and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the existence of the Reading Corner in the school had a positive impact on students' interest in reading, critical thinking skills, and increased students' ability to understand and convey information orally and in writing. In addition, teachers and school officials play an active role in managing and developing literacy activities through the Reading Corner, thus creating a learning environment that supports students' overall intellectual development.